Tinjauan Yuridis Sengketa Peralihan Hak Atas Tanah Hibah Ditinjau Berdasarkan Peraturan Perundang-Undangan - Afrizal Pramudito, Muhammad; Djayaputra, Gunawan (UNES Law Review, 2023)
Soil is a source of life not only for humans but for every living creature on earth such as animals and plants. In the Civil Code, land is categorized as immovable objects in accordance with Article 506 of the Civil Code. The transfer of land rights in the form of a grant is often a problem in people's lives. The definition of a gift is regulated in Article 1666 of the Civil Code, namely: "A gift is an agreement whereby the donor, during his or her lifetime, freely and irrevocably hands over an object for the needs of the recipient of the gift who receives the gift. That. The law does not recognize other gifts other than gifts between living people." The research method used is normative legal research. Normative juridical method writing is a writing method that is carried out by researching library material. The nature of the research used is analytical descriptive where the writing team tries to describe the transfer of grants that are not registered with PPAT or known as verbal grants according to the applicable laws and regulations. The transfer of land rights must be proven by an authentic deed issued by the PPAT or Land Office in the area where the dispute occurs. Giving a gift orally without a PPAT deed is considered invalid even though it meets the legitimacy of the portie, but the transition is still used verbally without any authentic evidence. Legal certainty for grant recipients is regulated in Article 37 of Government Regulation 40 of 1997 concerning Land Registration which states that the transfer of land rights and ownership rights to apartment units is through sale and purchase, exchange, grant, entry into a company and other legal acts of transfer of rights. In proving the validity of a Grant Deed, it must have external, formal and material evidential strength, and the process of making a Grant Deed fulfills the specified elements. Settlement of gift disputes is a deliberation between the heirs. Every grantor in providing a grant must openly state it in the PPAT deed so that it can be proven if a dispute occurs.